A new variant of killer-cell immunoglobulin-like receptor KIR3DL1*03101 isolated using sequence-based techniques. - Yindom, L; Wong, G; de Silva, T; Rowland-Jones, S (Blackwell Publishing Ltd, 2014)
The complete length genomic sequence of KIR3DL1*03101 differs from KIR3DL1*0010101 at multiple intronic and exonic sites.